The Effect of Business Performance Toward Sosial Performance and Maqashid Shariah Achievement at Islamic Banking - Tika Widiastuti; Imron Mawardi; Muhammad Nafik HR; Wahyuningsih Wahyuningsih; Imam Wahyudi Indrawan (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Islamic bank is a business and social institution. As a business institution, Islamic bank has an objective to develop value of share holder’s wealth: gain profit, have a good liquidity, efficient, etc. As a social institution,Islamic bank has to do social activity: collect and distribute zakah, infaq, shadaqah, and waqf; has a commitment to small-medium enterprise, and gives qard and qardhul hasan. Islamic bank use sharia (Islamic law) in operating a business, hence Islamic bank has to effort to attain the objective of sharia ormaqashid sharia (maslahah). This study aims to study the effect of business performance of Islamic bank toward social performance and attainment of maqashid sharia. This study use partial least square analysis, and found that (1) business performance significantly effect social performance and maqashid shariaattainment that measured by employee’s welfare (2) social performance significantly effect on maqashid sharia attainment. This study concluded that Islamic banks in Indonesia had a good commitment to practice sharia, concern to social activity and had effort to achieve the objective of sharia, that was maqashid sharia.